Combining ability analysis for yield and yield components in bold grained rice (oryza sativa l.) of assam (2009)
Combining ability analysis for grain yield and its components was carried out in eight parental diallel crosses of bold grained rice excluding reciprocals. The general combining ability (GCA) and specific combining ability (SCA) effects were significant for all the characters indicating the importance of both additive and non-additive gene effects in their inheritance. The parents Ranjit followed by Matonga and Monohar Sali contributed significantly to high GCA effect towards high grain yield per hill. The superior specific cross combinations for high grain yield per hill were Matonga/Bar Madhava, originated from high x low GCA combination followed by Dhola Mula/ Ranjit (low x high gca), Chandmoni/Hathi Sali (low x high GCA), Dhola Mula/Mala (low x low gca), Matonga/Mala (high x low GCA), Bar Madhava/Hathi Sali (low x high GCA) and Matonga/Hathi Sali (high x high GCA). Further, these crosses exhibited high SCA effects for some other characters as well.